Strategy to Improve the Quality of Corn Kernels Through the Analytical Hierarchical Process Approach - Miranti Putry; Ayu Puspitasari (Enrichment : Journal of Management, 2022)
Corn is the main component of the feed industry, 50% of corn production in Indonesia is used to meet the needs of the feed industry, while only about 30% is for consumption. And the rest is for other industrial needs. The quality of corn harvested by farmers is important for feed producers to produce quality feed according to applicable quality standards. For this reason, it is necessary to apply an appropriate quality improvement strategy using the AHP (Analytical Hierarchical Process) method. The results of the analysis of factors that affect the quality of corn Kernels are harvesting techniques, and one alternative that needs to be done in controlling the quality of corn Kernels is the application of quality control.